Catálogo de intensidades de linhas de emissão de remanescentes de supernovas e aplicações - Pauletti, Diogo (2011)
Emission line intensities from ionized nebulae are an important information source about this objects. There are many data on line intensities emitted from supernova remnants scattered in the literature. However, these data can be more efficiently used if avaliable in the form of an electronic data base. Based on this, it was made a catalog of emission line intensities of supernova remnants with data obtained from the literature, including lines in the spectral range of 900Å to 100 mm. About 300 supernova remnants and more than 25 000 emission line intensities were cataloged, including adittional information associated to the objects and the observations. As a demonstration of the aplicability of this catalog, diagnostic diagrams were made with emission line intensities from supernova remnants and from HII regions, using the line ratios [O III] l5007/Hb, [N II] l6583/Ha, [O II] l3727/Hb, [S II] (l6716+l6730)/Ha and [O I] l6300/Ha. Besides these traditional diagrams, the large amount of data in the catalog allowed the construction of others diagrams using relatively weak lines, rarely measured. The diagrams were effective for the classification and discrimination of these classes of objects. It was also verified the values of the ratios [O III] l5007/l4959 and [N II] l6584/l6548, which returned results in agreement with some others published. Moreover, considering the ultraviolet spectroscopy advances in recent decades, it is presented an history of the instrumentation and its performance evolution, regarding some topics that show the importance of the studies about the ultraviolet spectra of supernova remnants. Finally, a list of all ultraviolet emission lines already measured in supernova remnants until 2010 was made, and compared with a similar list created in 1996. It was found that many new lines were detected and some multiplets became resolved since then. Each one of the 142 lines was identified by its wavelength, the ion and parameters of the transition that generates it. This table may be used as a reference for identifying emission lines in supernova remnants in future studies.